Development of Interactive Learning Media Based on Motion Graphic Animation for Basic Photography Subject - Yayang Yusmaningsih; Vera Irma Delianti; Lativa Mursyida; Rizkayeni Marta (Sagamedia Teknologi Nusantara, 2024)
This study aims to design and develop interactive multimedia-based learning media utilizing motion graphic animation for the Basic Photography subject at SMK Negeri 4 Padang. This media was designed to assist students in understanding the material more effectively and engagingly. The method used is the Multimedia Development Life Cycle (MDLC), consisting of six stages: concept, design, material collecting, assembly, testing, and distribution. The validity test involved four experts, two media experts, and two material experts, while the practicality test involved ten students from Class X DKV A. The results of the validity test show that the learning media is highly valid, with Aiken's V score of 0.94 for both media and material aspects. The practicality test yielded an average score of 90.13%, categorized as